Proximate Analysis of Hotong Buru (Setaria italica) As A Culinary Material in Southern Buru Regency - Ali Awan; Muhammad Tarmizi Kubangun; Tri Santi Kurnia (SCIENCE NATURE, 2021)
Hotong Buru (S. italica) is a kind of cogon grass originating from the island of Buru. This plant produces seeds that are used as a very potential alternative food for rice because this plant can grow on various types of soil, even on sandy soils. Proximate analysis is a chemical test to determine the nutrient content of a feed or a feed raw material. Moreover, Hotong seeds have a protein content of around 11.2% and about 2.4% fat, while rice has a protein content of around 4.5% and 1-2% fat, which means that the protein and fat contents of Hotong seeds are over twice higher than that in rice. Judging from the carbohydrate content, the content of Hotong seeds is around 73%, almost the same as the carbohydrate content in rice, which is around 70-80%. This research was conducted to determine the nutritional content of Hotong Buru as a culinary ingredient. The research was conducted in the area of ​​South Buru Regency, namely processing Hotong Buru as a culinary ingredient, and in Baristand Ambon, namely proximate analysis. The results of the proximate analysis of 10 types of Hotong Buru in culinary preparations, resulted in the discovery of carbohydrate content with an average of 75.04, protein content with an average of 17.98, fat content with an average of 6.54, and fiber content with an average of 3.67, this proves that the nutritional content of culinary Hotong Buru is very high and can be used as the right staple substitute for rice